2005
DOI: 10.2186/prp.4.32
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Thin Hydroxyapatite Layers Formed on Anodic Oxide Titanium after Hydrothermal Treatment in Rat Bone Marrow Cell Culture

Abstract: Clinical significanceSuccessful osseointegration requires careful characterization of the thin hydroxyapatite (HA)layer formed on commercially pure titanium during anodization and hydrothermal treatment. This study indicates that the thin HA layer appears to stabilize during the process of bone matrix mineralization in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…A HA/cpTi surface is compatible with bone tissue,16 and has no adverse effect on immune cells 17. Furthermore, the thin HA layer formed on HA/cpTi increases in stability during the process of bone matrix mineralization 18. These data suggest that the chemical or physical state of the HA/cpTi surface influences the phenotypic expression of cells involved in bone formation.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…A HA/cpTi surface is compatible with bone tissue,16 and has no adverse effect on immune cells 17. Furthermore, the thin HA layer formed on HA/cpTi increases in stability during the process of bone matrix mineralization 18. These data suggest that the chemical or physical state of the HA/cpTi surface influences the phenotypic expression of cells involved in bone formation.…”
Section: Introductionmentioning
confidence: 90%
“…The morphology of the HA crystals was observed by scanning electron microscopy (SEM) (S‐2300; Hitachi, Tokyo, Japan), which showed that approximately 60% of the surface of the AOFCP was covered with HA crystals 10–12. The precipitated HA crystals were a typical single hexagonal columnar shape and had very high crystallinity 10, 11, 13, 18. This film had a lamellar structure; a thin HA layer of 1 μm was formed on an AOFCP of 4.5 μm, making a total film thickness of 5.5 μm 11.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One important aspect of the HA coating is its thickness. Thin HA coatings have been found to remain stable during bone matrix mineralization [13], while thicker HA coatings might crack and/or delaminate, with a risk of particulate release [14]. Thin HA coatings have also been shown to promote the same osteogenic response as thicker coatings [8].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past sixty years, titanium has been investigated for biomedical applications based on its good biocompatibility (1,2), stability (2)(3)(4), and mechanical properties (2,3). In fact, titanium and titanium alloys osseointegrate with the surrounding bone without forming a fibrous intermediate layer between bone and the implant (5). Fibrous intermediates can delay healing and result in micromotion, ultimately leading to implant failure.…”
Section: Introductionmentioning
confidence: 99%